Association of publication record and independent NIH funding. - Kenneth A Michelson (PLoS ONE, 2022)
Background Publications may be a modifiable factor toward research project grant (RPG) funding decisions, the objective was to determine the association of publication record with later RPG receipt. Methods This was a retrospective cohort study of recipients of K01, K08, or K23 US career development awards (CDAs) starting from 2000-2015. Exposures were CDA awardees' first-, middle-, and last-author publication counts, and the quartile of awardees' highest and mean publication impact factors. The independent association of each exposure with time to RPG (R01 or equivalent) was determined using a Cox model, after adjustment for CDA type, awardee change in institution, and institutional CDA count. The proportion of CDA recipients with later independent funding was also determined by publication count. Results Among 6744 CDA awardees, 3943 obtained an RPG. The median time to RPG was 5.6 years (interquartile range 4.2-7.5). The number of first-authorships was associated with a shorter time to RPG (1-4 versus 0: hazard ratio [HR] 1.22, 95% confidence interval [CI] 1.10-1.36; 5-9: 1.59, 95% CI 1.40-1.79; 10-24: 1.78, 95% CI 1.54-2.07; 25+: 2.40, 95% CI 1.61-3.56). Last-authorships were associated with a shorter time to RPG (1-4 versus 0: HR 1.99, 95% CI 1.83-2.16; 5-9: 2.72, 95% CI 2.45-3.03; 10-24: 3.17, 95% CI 2.78-3.62; 25+: 3.12, 95% CI 2.17-4.50). Higher maximum impact factor was associated with a shorter time to RPG (Q2 versus lowest: HR 1.28, 95% CI 1.12-1.46; Q3: 1.45, 95% CI 1.24-1.70; Q4: 1.67, 95% CI 1.39-2.02). Mean impact factor and middle-authorships were not associated with time to RPG. Among 687 CDAs with zero associated first- or last-authorships, 158 (23%) achieved later RPG funding. Among those with at least 10 total first- or last-authorships, 1288/1554 (83%) obtained a later RPG. Conclusions A higher number and impact of publications was associated with later independent funding.